Assessing the Viability of Religious Education in Shaping Moral Behavior: The Context of Lesotho - Mokotso, Rasebate (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This research examines whether religious studies as a school subject effectively cultivate virtues and values as mandated by the curriculum, which reflects national educational goals. The study uses qualitative content analysis to explore the key educational documents, such as the syllabus and summative assessment question papers from both national and school-based evaluations. While Kohlberg’s moral development framework emphasizes reasoning and critical thinking, this research found significant challenges in the religious studies syllabus and assessments including misalignment between the syllabus and curriculum, insufficient focus on values in assessments, and poorly structured questions on values and virtues. The study recommends addressing these issues by bridging the educational disconnect, fostering reflective citizenship, and designing more holistic assessments.